Whole blood microRNA expression may not be useful for screening non-small cell lung cancer - Patnaik, Santosh K. (PLoS One, 2017)
At least seven studies have suggested that microRNA levels in whole blood can be diagnostic for lung cancer. We conducted a large bi-institutional study to validate this. Qiagen(®) PAXgene(™) Blood miRNA System was used to collect blood and extract RNA from it for 85 pathologic stage I-IV non-small cell lung cancer (NSCLC) cases and 76 clinically-relevant controls who had a benign pulmonary mass, or a high risk of developing lung cancer because of a history of cigarette smoking or age >60 years. Cases and controls were similar for age, gender, race, and blood hemoglobin and leukocyte but not platelet levels (0.23 and 0.26 million/μl, respectively; t test P = 0.01). Exiqon(®) MiRCURY(™) microarrays were used to quantify microRNAs in RNA isolates. Quantification was also performed using Taqman(™) microRNA reverse transcription (RT)-PCR assays for five microRNAs whose lung cancer-diagnostic potential had been suggested in seven published studies. Of the 1,941 human mature microRNAs detectable with the microarray platform, 598 (31%) were identified as expressed and reliably quantified among the study's subjects. However, none of the microRNAs was differentially expressed between cases and controls (P >0.05 at false discovery rate <5% in test using empirical Bayes-moderated t statistics). In classification analyses with leave-one-out internal cross-validation, cases and controls could be identified by microRNA expression with 47% and 50% accuracy with support vector machines and top-scoring pair methods, respectively. Cases and controls did not differ for RT-PCR-based measurements of any of the five microRNAs whose biomarker potential had been suggested by seven previous studies. Additionally, no difference for microRNA expression was noticed in microarray-based microRNA profiles of whole blood of 12 stage IA-IIIB NSCLC cases before and three-four weeks after tumor resection. These findings show that whole blood microRNA expression profiles lack diagnostic value for high-risk screening of NSCLC, though such value may exist for selective sub-groups of NSCLC and control populations.